Hubungan kadar hemoglobin dengan peluang remisi pada anak penderita leukemia limfoblastik akut periode 2010-2014 di RSUP Prof. Dr. R. D. Kandou Manado - Tewuh, Sharon; Mantik, Max F.J.; Warouw, Sarah M. (e-CliniC, 2016)
Abstract: Acute lymphocytic leukemia (ALL), also called acute lymphoblastic leukemia, is a cancer that starts from the initial stem cells of the lymphocytes in the bone marrow. This study aimed to determine the relationship of hemoglobin level with the chance of remission in children with ALL. This was an analytical retrospective study. Data were obtained from the medical records of Estella at Prof. Dr. R. D. Hospital period 2010-2014 with a total samples of 30 patients. The Fisher exact test showed a significant p value of 0.019 (p <0.05). Conclusion: There was a significant relationship between hemoglobin level and the chance of remission in patients with ALL. Keywords: hemoglobin level, remission, acute lymphoblastic leukemiaÂ Abstrak: Leukemia limfositik akut (LLA), juga disebut leukemia limfoblastik akut, adalah kanker yang dimulai dari sel stem awal dari limfosit dalam sumsum tulang. Penelitian ini bertujuan untuk mengetahui hubungan kadar Hb dengan peluang remisi pada anak penderita LLA. Jenis penelitian ini ialah analitik retrospektif dengan menggunakan data rekam medik di ruang Estella RSUP Prof. Dr. R. D. Kandou periode 2010-2014 dengan sampel sebanyak 30 pasien. Hasil uji Fisher exact test menunjukkan nilai signifikasi p=0,019 (p<0,05). Simpulan: Terdapat hubungan bermakna antara kadar Hb dengan peluang remisi pada pasien LLA.Kata kunci: kadar Hb, remisi, LLA